Food Security in Bangladesh: Patterns, Determinants, Interventions and Scope for Regional Cooperation. - Chatterjee, Biswajit and Kundu, Sangeeta (2011)
Food security is the condition in which all people at all times have both physical and economic access to sufficient food to meet their dietary needs for a productive and healthy life. In a poverty stricken country like Bangladesh, the issue of food insecurity for a large section of its population focuses on the need to develop appropriate policy designs to alleviate the conditions of the people and eliminate endemic hunger .One such strategy has been the increasing cooperation with its neighbour India, where the conditions of food insecurity have long remained quite large and serious. According to the International Food Policy Research Institute (IFPRI), in terms of the Global Hunger Index (GHI) score, Bangladesh ranks 68 in 2010 just below India‘s 67, with GHI score of 24.2 compared to India‘s score of 24.1. Both India and Bangladesh belong to the categories of extremely alarming and alarming undernutrition and hunger in 1990 and 2010, as their GHI scores have moved from more than 30 to more than 20 between these two periods. Lack of agricultural lands, employment opportunities, social services, access and knowledge of nutritional diet and healthcare, sanitation and safe drinking water coupled with sustained poverty leave a significant portion of the Bangladesh population hungry and malnourished.There exists scope for regional cooperation between India and Bangladesh in the context of mitigating the challenges of food security through(a) flood control and expansion of irrigation facilities to the farmers in Bangladesh,(b) the open free trade agreement with India such that surplus foodgrains from India could enter Bangladesh markets to minimize the adverse effects of food price inflation , (c)SAARC Food Bank led by India to support and supplement its national efforts to provide food security to the people of the region, and (d) though development of IT based food distribution mechanism with India‘s technical support , and also (e) through cooperation between India and Bangladesh in the domain of poverty alleviation.